The Effects of Anterior Cruciate Ligament Deficiency on the Meniscus and Articular Cartilage: A Novel Dynamic In Vitro Pilot Study. Issue 4 (1st April 2016) - Arner, Justin W.; Irvine, James N.; Zheng, Liying; Gale, Tom; Thorhauer, Eric; Hankins, Margaret; Abebe, Ermias; Tashman, Scott; Zhang, Xudong; Harner, Christopher D.
Background: Anterior cruciate ligament (ACL) injury increases the risk of meniscus and articular cartilage damage, but the causes are not well understood. Previous in vitro studies were static, required extensive knee dissection, and likely altered meniscal and cartilage contact due to the insertion of pressure sensing devices. Hypothesis: ACL deficiency will lead to increased translation of the lateral meniscus and increased deformation of the medial meniscus as well as alter cartilage contact location, strain, and area. Study Design: Descriptive laboratory study. Methods: With minimally invasive techniques, six 1.0-mm tantalum beads were implanted into the medial and lateral menisci of 6 fresh-frozen cadaveric knees. Dynamic stereo x-rays (DSXs) were obtained during dynamic knee flexion (from 15° to 60°, simulating a standing squat) with a 46-kg load in intact and ACL-deficient states. Knee kinematics, meniscal movement and deformation, and cartilage contact were compared by novel imaging coregistration. Results: During dynamic knee flexion from 15° to 60°, the tibia translated 2.6 mm ( P = .05) more anteriorly, with 2.3° more internal rotation ( P = .04) with ACL deficiency. The medial and lateral menisci, respectively, translated posteriorly an additional 0.7 mm ( P = .05) and 1.0 mm ( P = .03). Medial and lateral compartment cartilage contact location moved posteriorly (2.0 mm [ P = .05] and 2.0 mm [ P = .04], respectively). Conclusion: The lateral meniscus showed greater translation with ACL deficiency compared with the medial meniscus, which may explain the greater incidences of acute lateral meniscus tears and chronic medial meniscus tears. Furthermore, cartilage contact location moved further posteriorly than that of the meniscus in both compartments, possibly imparting more meniscal stresses that may lead to early degeneration. This new, minimally invasive, dynamic in vitro model allows the study of meniscus function and cartilage contact and can be applied to evaluate different pathologies and surgical techniques. Clinical Relevance: This novel model illustrates that ACL injury may lead to significant meniscus and cartilage abnormalities acutely, and these parameters are dynamically measurable while maintaining native anatomy.